2024
DOI: 10.1007/s00405-023-08372-4
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of large language models in managing odontogenic sinusitis clinical scenarios: a preliminary multidisciplinary evaluation

Alberto Maria Saibene,
Fabiana Allevi,
Christian Calvo-Henriquez
et al.

Abstract: Purpose This study aimed to evaluate the utility of large language model (LLM) artificial intelligence tools, Chat Generative Pre-Trained Transformer (ChatGPT) versions 3.5 and 4, in managing complex otolaryngological clinical scenarios, specifically for the multidisciplinary management of odontogenic sinusitis (ODS). Methods A prospective, structured multidisciplinary specialist evaluation was conducted using five ad hoc designed ODS-related clinical scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Some authors have even proposed investigating the potential benefits of artificial intelligence in decision-making for ODS scenarios. Saibene et al demonstrated the potential for AI to complement evidence-based clinical decision making, although there was still substantial disagreement between AI and clinical decisions, suggesting that AI is not yet optimal in assisting clinical management conclusions [61].…”
Section: Treatmentsmentioning
confidence: 99%
“…Some authors have even proposed investigating the potential benefits of artificial intelligence in decision-making for ODS scenarios. Saibene et al demonstrated the potential for AI to complement evidence-based clinical decision making, although there was still substantial disagreement between AI and clinical decisions, suggesting that AI is not yet optimal in assisting clinical management conclusions [61].…”
Section: Treatmentsmentioning
confidence: 99%